A clinical survey on the prevalence and types of cheek teeth disorders present in 400 Zamorano‐Leonés and 400 Mirandês donkeys (Equus asinus). (14th December 2013) - Rodrigues, J. B.; Dixon, P. M.; Bastos, E.; San Roman, F.; Viegas, C.
Abstract : Dental disease is now recognised as a major but often unrecognised disorder of equids, including horses and donkeys. However, very few large clinical studies have documented the prevalence and type of dental disease present in different equid populations and no dental studies have been reported in Zamorano‐Leonés or Mirandês donkeys, two endangered donkey breeds. Clinical and detailed oral examinations were performed in 400 Mirandês and 400 Zamorano‐Leonés donkeys in Portugal and Spain. It was found that just 4.5 per cent had ever received any previous dental care. Cheek teeth (CT) disorders were present in 82.8 per cent of these donkeys, ranging from a prevalence of 29.6 per cent in the <2.5‐year‐old group to 100 per cent in the >25‐year‐old group. These CT disorders included enamel overgrowths (73.1 per cent prevalence but with just 6.3 per cent having associated soft tissue injuries), focal overgrowths (37.3 per cent), periodontal disease (23.5 per cent) and diastemata (19.9 per cent). Peripheral caries was present in 5.9 per cent of cases, but inexplicably, infundibular caries was very rare (1.3 per cent prevalence); this may have been due to their almost fully foraged diet. The high prevalence of enamel overgrowths in these donkeys, most which never received concentrates, also raises questions about the aetiology of this disorder. This very high prevalence of CT disorders, especially in older donkeys, was of great welfare concern in some cases and emphasises the need for routine dental care in these cases on welfare grounds and in order to help preserve these unique breeds.